Hubungan antara Kepribadian Hardiness dan Status Pernikahan dengan Fear of Success pada Wanita Karier yang Sudah Menikah - Afifah Dinillah; Supriyati Supriyati; Prida Harkina (Observasi : Jurnal Publikasi Ilmu Psikologi, 2026)
The association between the variables hardiness Personality and Marital Status with Fear of success in Career Women is explored in this study. “The hypothesis of this study is that there is a significant relationship between the Relationship Between” hardiness Personality and Marital Status with Fear of success in Career Women. The subjects in this study were women who worked part-time (fulltime), aged 20-45 years and married, with a total of 130 subjects. Research data were taken using the Fear of success Scale, hardiness Personality Type Scale, and Marital Status Demographic Scale. The collected data were analyzed using multiple linear regression analysis techniques. The results of the analysis show that there is a significant relationship between hardiness Personality and Marital Status with Fear of success in Career Women (p<0.05) which means that the higher the level of fear of success, the higher the level of hardiness. The Fear of success variable can be explained by the hardiness Personality Type Variable with a result of 44.8%.